Can genetic polymorphisms predict response variability to anodal transcranial direct current stimulation of the primary motor cortex?. (3rd November 2020) - Pellegrini, Michael; Zoghi, Maryam; Jaberzadeh, Shapour
Abstract: Genetic mediation of cortical plasticity and the role genetic variants play in previously observed response variability to transcranial direct current stimulation (tDCS) have become important issues in the tDCS literature in recent years. This study investigated whether inter‐individual variability to tDCS was in‐part genetically mediated. In 61 healthy males, anodal‐tDCS (a‐tDCS) and sham‐tDCS were administered to the primary motor cortex at 1 mA for 10‐min via 6 × 4 cm active and 7 × 5 cm return electrodes. Twenty‐five single‐pulse transcranial magnetic stimulation (TMS) motor evoked potentials (MEP) were recorded to represent corticospinal excitability (CSE). Twenty‐five paired‐pulse MEPs were recorded with 3 ms inter‐stimulus interval (ISI) to assess intracortical inhibition (ICI) via short‐interval intracranial inhibition (SICI) and 10 ms ISI for intracortical facilitation (ICF). Saliva samples were tested for specific genetic polymorphisms in genes encoding for excitatory and inhibitory neuroreceptors. Individuals were sub‐grouped based on a pre‐determined threshold and via statistical cluster analysis. Two distinct subgroups were identified, increases in CSE following a‐tDCS (i.e. Responders) and no increase or even reductions in CSE (i.e. Non‐responders). No changes in ICI or ICF were reported. No relationships were reported between genetic polymorphisms in excitatory receptor genes and a‐tDCS responders. An association was reported between a‐tDCS responders and GABRA3 gene polymorphisms encoding for GABA‐A receptors suggesting potential relationships between GABA‐A receptor variations and capacity to undergo tDCS‐induced cortical plasticity. In the largest tDCS study of its kind, this study presents an important step forward in determining the contribution genetic factors play in previously observed inter‐individual variability to tDCS. Abstract : Following anodal transcranial direct current stimulation (a‐tDCS) individuals were subgrouped as either those who responded as expected (i.e. responders) or those who did not (i.e. non‐responders). A‐tDCS response subgrouping was not associated with single nucleotide polymorphisms (SNPs) in genes encoding for N ‐methyl‐d ‐aspartate (NMDA) receptors. SNPs in a gamma‐aminobutyric acid A (GABA‐A) receptors gene (i.e. GABRA3) was associated with a‐tDCS responders and may predict response to a‐tDCS.